TINJAUAN HUKUM PERLAKUAN PERPAJAKAN ATAS TANAH INBRENG DAN BANGUNAN - Rafiqi Rafiqi (Universitas Medan Area, 2016)
In Country have people and industrial pay to country, Inbreng pajak In Indonesia mustcount adaption Indonesia, a Enterprenuer must register Indonesia. Pasiva and Aktivainbreng in Industrial must give account According to the prevailing stipulation the sellingand buying on land.